Elevated faecal calprotectin is linked to worse disease status in axial spondyloarthritis: results from the SPARTAKUS cohort. (15th January 2019) - Olofsson, Tor; Lindqvist, Elisabet; Mogard, Elisabeth; Andréasson, Kristofer; Marsal, Jan; Geijer, Mats; Kristensen, Lars Erik; Wallman, Johan K
Abstract: Objectives: To examine faecal calprotectin (F-calprotectin) levels and presence of anti- Saccharomyces cerevisiae antibodies (ASCA) and their associations with disease subtype and current status in axial SpA (axSpA). Methods: F-calprotectin and ASCA in serum were compared between consecutive patients with a clinical axSpA diagnosis, classified as non-radiographic axSpA (nr-axSpA; n = 40) or AS ( n = 90), and with healthy controls ( n = 35). Furthermore, standard axSpA outcome measures were compared between axSpA patients (nr-axSpA and AS combined) with elevated vs normal F-calprotectin, ASCA IgA and IgG, respectively. Results: Elevated F-calprotectin (⩾50 mg/kg) was observed in 27% of nr-axSpA patients, 38% of AS patients and 6% of controls. F-calprotectin was significantly higher in AS vs nr-axSpA [AS: geometric mean 41 (95% CI 32, 54) mg/kg; nr-axSpA: 24 (95% CI 16, 38) mg/kg; P = 0.037], and in each axSpA subtype vs controls. Overall, worse disease activity and physical function scores were observed among axSpA patients with elevated vs normal F-calprotectin levels, with significant differences regarding patient's visual analogue scale for global health, ASDAS using CRP, and BASFI (adjusted for age, sex, NSAID use, anti-rheumatic treatments, and CRP). ASCA titres and seropositivity (⩾10 U/ml) were similar in nr-axSpA (IgA/IgG-seropositivity: 8%/26%) and AS (7%/28%), and clinical outcome measures did not differ between patients with elevated vs normal ASCA IgA or IgG, respectively. Compared with controls (IgA/IgG-seropositivity: 0%/17%), ASCA IgA was significantly higher in both axSpA subtypes, and IgG was significantly higher in the AS group. Conclusion: In patients with axSpA, gut inflammation measured by elevated F-calprotectin is associated with worse disease activity and physical function, and may be a marker of more severe disease.